Peningkatan Minat Belajar Ipa Melalui PenerapanStrategi Pembelajaran Explicit Instruction BagiSiswa Kelas V Sd N Klari 2 KaranggedeTahun Ajaran 2015/2016 - Sadono, Muh. Setiawan, Drs. Mulyadi S.K, M.Pd (2017)
Background: Master only use the lecture method resulted in low student interest.So also for teaching science in ementary N 2 Karanggede Klari, requiredlearning strategies useful to improve the quality of the learning process. Learningstrategy chosen is learning strategy Explicit Instruction.Objective: To increase interest and student learning outcomes in science subjectsthrough the application of learning strategies Explicit Instruction.Benefits Research: Provides insight to the world of education on improvinglearning in science subjects by learning strategies Explicit InstructionMethods: This study included a Class Action Research (PTK). Subjects wereteachers and students of class V SD N Klari 2 Karanggede, Boyolali totaling 21 students.Teknik collecting data through interviews, observation, documentation,and tes.Teknik using descriptive qualitative data analysis with interactive analysis consists of three phases, which are data reduction , exposure data and conclusionswithdrawal.Results: Showing an increase in student interest that impact on student learning outcomes so that an increase in science subjects on material energy and change.It can be seen from the results of the implementation of learning that showincreased interest in learning was reflected dalamPerasaan happy passionate students in learning and interested in learning with prasiklus percentage of 57.1%,69.0% the first cycle, the second cycle students to 83.3% . interest teachers and liked the initiative to learn on the initial conditions of 54.7%, 66.6% the firstcycle, the second cycle 82.1%. attention concentration of students in learning and meticulous in studying the initial conditions 55.9%, 66.6% the first cycle, thesecond cycle of 80.9%. The involvement of the students have a willingness tolearn and tenacious in learning in the initial conditions 55.9%, 71.4% the first cycle, the second cycle of 78.5%. Science learning results on the initial conditionsof 51.1%, 70.2% the first cycle, the second cycle of 80.9%. Student learningoutcomes also increased. It can be seen from the results of theimplementation ofthe learning process before the action amounted to 47.61% of students whocompleted the study and after the action has increased by 57.14% in the first cycle, and in the final act of complete student in learning increased to 90.47%The conclusion of the study: Application of Explicit Instruction learningstrategies can increase interest and class V student learning outcomes in science subjects in SDN Klari 2 Karanggede, Boyolali academic year 2013/2014.